Time to publication among completed diagnostic accuracy studies: associated with reported accuracy estimates - Korevaar, Daniël A. (BMC Med Res Methodol, 2016)
BACKGROUND: Previous evaluations have documented that studies evaluating the effectiveness of therapeutic interventions are not always reported, and that those with statistically significant results are published more rapidly than those without. This can lead to reporting bias in systematic reviews and other literature syntheses. We evaluated whether diagnostic accuracy studies that report promising results about the performance of medical tests are also published more rapidly. METHODS: We obtained all primary diagnostic accuracy studies included in meta-analyses of Medline-indexed systematic reviews that were published between September 2011 and January 2012. For each primary study, we extracted estimates of diagnostic accuracy (sensitivity, specificity, Youden’s index), the completion date of participant recruitment, and the publication date. We calculated the time from completion to publication and assessed associations with reported accuracy estimates. RESULTS: Forty-nine systematic reviews were identified, containing 92 meta-analyses and 924 unique primary studies, of which 756 could be included. Study completion dates were missing for 285 (38 %) of these. Median time from completion to publication in the remaining 471 studies was 24 months (IQR 16 to 35). Primary studies that reported higher estimates of sensitivity (Spearman’s rho = −0.14; p = 0.003), specificity (rho = −0.17; p < 0.001), and Youden’s index (rho = −0.22; p < 0.001) had significantly shorter times to publication. When comparing time to publication in studies reporting accuracy estimates above versus below the median, the median number of months was 23 versus 25 for sensitivity (p = 0.046), 22 versus 27 for specificity (p = 0.001), and 22 versus 27 for Youden’s index (p < 0.001). These differential time lags remained significant in multivariable Cox regression analyses with adjustment for other study characteristics, with hazard ratios of publication of 1.06 (95 % CI 1.02 to 1.11; p = 0.007) for logit-transformed estimates of sensitivity, 1.09 (95 % CI 1.04 to 1.14; p < 0.001) for logit-transformed estimates of specificity, and 1.09 (95 % CI 1.03 to 1.14; p = 0.001) for logit-transformed estimates of Youden’s index. CONCLUSIONS: Time to publication was significantly shorter for studies reporting higher estimates of diagnostic accuracy compared to those reporting lower estimates. This suggests that searching and analyzing the published literature, rather than all completed studies, can produce a biased view of the performance of medical tests. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12874-016-0177-4) contains supplementary material, which is available to authorized users.